Mutual Fund Herding and the Impact on Stock Prices - Wermers, Russ (Journal of Finance, 1999)
We analyze the trading activity of the mutual fund industry from 1975 through 1994 to determine whether funds “herd” when they trade stocks and to investigate the impact of herding on stock prices. Although we find little herding by mutual funds in the average stock, we find much higher levels in trades of small stocks and in trading by growth‐oriented funds. Stocks that herds buy outperform stocks that they sell by 4 percent during the following six months; this return difference is much more pronounced among small stocks. Our results are consistent with mutual fund herding speeding the price‐adjustment process.